Iron Status in Chronic Renal Failure with Anemia - Khanam, Shaheda; Begum, Noorzahan; Hoque, AMM Ehteshamul (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Background: Chronic renal failure (CRF) is a major public health hazard. Anemia is an accompaniment and independent risk factor for the development of cardiac dysfunction and responsible for 40% to 50% deaths in CRF patients. For this reason, effective erythropoiesis to correct anemia by erythropoietin therapy and maintenance of target iron level is very much important. Subjects and Methods: The present study has been designed to observe iron status in different stages of CRF patients suffering from anemia. For this purpose, 65 male CRF patients with anemia and 25 healthy male (control) subjects, in the age group of 3050 years were selected randomly from BSMMU outpatient department. Iron level, hemoglobin and creatinine clearance were estimated by usual laboratory technique. Data were analyzed statistically by ANOVA and Pearsons correlation coefficient test. Among 65 CRF patients, 15 were mild, 25 were moderate and 25 were reported severe renal failure with anemia. Results: The mean serum iron, transferrin saturation and ferritin were significantly (P < 0.001) lower in moderate but severe in CRF patients with anemia compared to those of healthy subjects and these values were also significantly (P < 0.001) lower in severe CRF than those of mild and moderate groups of patients. On the other hand, total iron binding capacity was significantly (P < 0.001) higher only in severe group of CRF patients compared to healthy, mild and moderate group of CRF patients. In addition, 72% severe group of CRF patients had serum ferritin and 28% had transferrin saturation below the target level (?100 ng/ml serum ferritin & ?20% transferrin saturation). Decreasing iron status which is more marked in severe CRF patients are suggestive of iron deficiency and iron status below the target level in severe CRF patients indicate inadequate iron store. Also, a significantly (P < 0.001) decreasing hemoglobin concentration is observed in severe CRF case compared to those of mild and moderate CRF patients with anemia. Conclusion: From the present study it may be concluded that changes in iron status occur in CRF patients with anemia and these changes vary along with severity of CRF. DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i1.21 Chatt Maa Shi Hosp Med Coll J 2013; 12(1): 12-17